Διάβρωση και μεταλλογραφική ανάλυση διάφορων τύπων χάλυβα οπλισμού που χρησιμοποιήθηκαν σε κατασκευές οπλισμένου σκυροδέματος στην Κύπρο - Κοκολάκης, Δημήτριος (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
One of the main problems which concern a Civil Engineer nowadays is steel corrosion in reinforced concrete structures. At Cyprus this frequented phenomenon is justified because Cyprus is an island country. This research intent to analyze the mechanism of steel corrosion and the metallurgical analysis of corroded and not corroded specimens of RC steel rebars, in order to correlate the crystal structure of steel with corrosion. Additionally, another aim of this research is to define how the elaboration of steel can lead to corrosion. This research is divided into six chapters, from which the first one is an introductory chapter, which introduces the reader in the meaning of RC and in the meaning of corrosion, providing information about the materials which compose RC and also providing information about causes of steel corrosion. In the second chapter an integrated report about steel rebar is made, providing information relevant to the elements which compose steel rebars and the process by which steel rebars are made. Furthermore second chapter contains information about steel corrosion and metallurgical analysis. The third chapter contains similar researches of distinguished scientists. The research is continued with the fourth chapter in which the followed methodology of the experimental part of the dissertation is presented. Afterwards in the fifth chapter, the results of the study are analyzed. Summarizing, the sixth chapter contains the conclusions from this study, the most important of them is the lack of martensite in old RC steel rebars.
Keywords: Steel Corrosion; Reinforced Concrete; Steel; Διάβρωση Χάλυβα Οπλισμού; Οπλισμένο Σκυρόδεμα; Χάλυβας